7. Two-Dose 4CMenB Vaccination in Adolescents Elicits a Bactericidal Activity against 15 Outbreak-Representative Meningococcal Strains. (31st December 2020) - Biolchi, Alessia; Tomei, Sara; Santini, Laura; Gaetana, Rita La; Mori, Elena; Novy, Patricia; Rappuoli, Rino; Bekkat-Berkani, Rafik; Giuliani, Marzia Monica; Pizza, Mariagrazia; Sciences, Biological
Abstract: Background: Meningococcal outbreaks have often been associated with N. meningitidis serogroup B (MenB) in high-income countries. We examined whether antibodies elicited by the 4-component MenB vaccine (4CMenB) in adolescents could induce complement-mediated bacterial killing of a panel of 14 genetically diverse MenB strains representative of outbreaks that occurred from 2001 to 2016 (11 from the US, 2 from the UK, and 1 from France). One N. meningitidis serogroup W (MenW) hyperendemic strain (UK, 2011) was also included in the analysis. Methods: In a previous multicenter study (NCT02212457), adolescents aged 10-18y received 2 4CMenB doses 2 months apart. We tested individual sera collected from a subgroup of 20 US participants at pre-vaccination and 1 month post-second dose in a serum bactericidal assay with human complement (hSBA) against the meningococcal strain panel. Similarly, sera collected from 23 Chilean adolescents aged 11-17y (NCT00661713) were tested in a hSBA against a subset of 4 strains (3 from the US, 1 from the UK). Results: At baseline, the percentage of US subjects with seroprotective titers (hSBA ≥ 1:4) ranged from 5% to 35%. One month after 4CMenB series completion, 65% to 100% had seroprotective titers (hSBA ≥ 1:4) against 11 out of the 14 MenB tested strains. The seroprotection rate was 45%, 25%, and 15% against the 3 remaining MenB strains. Against MenW, the percentage of adolescents with hSBA titers ≥ 1:4 was 15% at baseline and 95% one month after series completion. No significant changes in the percentage of subjects were observed when analysing hSBA titers ≥ 1:8. Moreover, the subset analysis indicated similar results for US and Chilean subjects for 3 out of 4 strains: the percentage of US vs Chilean subjects with hSBA titers ≥ 1:4 was 100% vs 100%; 80% vs 74%; 45% vs 52%. For the 4th strain, 65% of US subjects vs 91% of Chilean subjects showed a hSBA ≥ 1:4. Conclusion: 4CMenB elicited bactericidal antibodies against a panel of 14 outbreak-representative MenB strains and 1 MenW hyperendemic strain in US adolescents. No major differences were detected in the bactericidal activity of Chilean subjects vaccinated with 4CMenB when tested against a subset of 4 MenB outbreak strains, suggesting that the immune response to 4CMenB is comparable in adolescents from different geographic areas. Disclosures: Alessia Biolchi, n/a, GSK (Employee) Sara Tomei, n/a, GSK (Employee) Laura Santini, n/a, GSK (Employee) Rita La Gaetana, n/a, GSK Vaccines (Employee, Shareholder) Elena Mori, n/a, GSK (Employee) Patricia Novy, PhD, GSK (Employee, Shareholder) Rino Rappuoli, PhD, GSK (Employee) Rafik Bekkat-Berkani, M.D, GSK (Employee, Shareholder) Marzia Monica Giuliani, n/a, GSK (Employee, Shareholder) Mariagrazia Pizza, Biological Sciences, PhD, GSK Vaccines (Employee)